Gaining a common understanding of transformation pathways in agri-food: Shared learning among partners of a Horizon Europe project - Frick, Rebekka; Roglic, Marija; Dentoni, Domenico; Home, Robert (The International Journal of Sociology of Agriculture and Food, 2025)
Researchers across scientific disciplines widely agree that agri-food systems need transformation, yet they rarely agree on the specific form this transformation should take. This study makes researchers' views of desirable agri-food systems transformation pathways explicit. Using the repertory grid methodology, we elicited personal constructs from researchers with expertise in 101 European initiatives, representing diverse scales, approaches, and objectives of transformation. Embedded in this methodology, personal construct elicitation reveals researchers' tacit knowledge and implicit assumptions. Results from this study reveal high convergence among researchers on the importance of stakeholder inclusion, autonomy, scope of ambitions, and anchoring in farming practices in transformation initiatives. However, researchers diverge in their views on how market orientation relates to transformative potential. Our findings demonstrate that while researchers broadly agree on key dimensions for describing transformation pathways in agri-food systems, they differ in their assessment of what makes initiatives truly transformative. Implications from these findings highlight the need for interdisciplinary research projects to reflect on how, when, and to what extent to engage in stakeholder participation and farmer engagement, as well as on whether transformative actions should be planned or emergent, and adaptive or disruptive, depending on the desired agri-food systems transformation.